Writing Descriptive Texts: What Makes this Difficult for Lower Secondary School Learners? - Nuralisaputri, Vina Virgianata; Megawati, Fika (Institut Agama Islam Negeri Palopo, 2023)
Many EFL learners who have spent years studying the language cannot perform well in writing. The difficulties in producing written English can hinder the success of learning English. Thus, this research aims to analyse the challenges that students commonly face in writing descriptive text. It employed a qualitative descriptive method to study the writing performance of seventh-grade EFL learners in one of the Indonesian junior high schools. Observation, students’ texts, and questionnaires were used to collect the data. The results of this study show that the difficulties in writing descriptive text concern language (vocabulary and language use), cognition (content, organisation, and mechanics), and psychological difficulties (feedback). The significant difficulty found in the students’ writing is reflected by mistakes made in language mechanics, which returned the lowest mean score (1.71). The other factors contributing to the students’ low writing performance are lack of vocabulary, of interest in learning English, and of understanding of language use and the structure of the text. Further factors include limited exposure to English writing activities – compounded by limited availability of dictionaries – as well as ineffective feedback from the teacher. Based on the results, it is suggested that teachers pay more attention to all aspects of challenges faced by students and their contributing factors by creating or providing creative and effective learning methods or media that can encourage students to achieve their learning objectives.Keywords: Students’ difficulties; Writing; Descriptive text